Implementasi model Project Based Learning (PJBL) pada mata kuliah perencanaan pembelajaran dalam merancang modul ajar berbasis Higher Order Thinking Skill (HOTS) - Isna Amanaturrakhmah (IKIP Siliwangi, 2023)
AbstractThis study aims to guide students in designing teaching modules that support the achievement of higher order thinking skills (HOTS). The methode that used is Classroom Action Research (CAR). The research subjects are the students at 4th semester of primary school teacher education major at STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu that consists of 35 students that determined by using purposive sampling method. The data collection techniques used were observation and documentation. Then the data were analyzed qualitatively. The results showed that students could carry out learning activities using the Project Based Learning (PjBL) model. 25 out of 35 research subjects succeeded in designing teaching modules based on Higher Order Thinking Skill (HOTS). 7 students develop modules with a scientific thinking skills orientation. 5 students succeeded in developing teaching modules with critical thinking skills orientation. 5 students succeeded in developing teaching modules oriented towards problem solving skills and 8 students succeeded in developing teaching modules oriented towards critical thinking skills. The implementation of the Project Based Learning (PjBL) model provides experiences in meaningful learning for students. In addition to gain theoretical insights, students also gain experience in developing a project of a HOTS-based teaching module. In the future students can develop their abilities in developing teaching modules in research/thesis as a final project.Â